Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5606/tftrd.2017.1007
|View full text |Cite
|
Sign up to set email alerts
|

Progression in acute ischemic stroke: Is widespread atherosclerotic background a risk factor?

Abstract: Objectives:In this study, we aimed to investigate the causes and conditions related with progression and outcome of progressive acute ischemic stroke. Patients and methods:In this prospective study, a total of 78 acute ischemic stroke patients (32 males, 46 females; mean age 70±12.8 years; range 34 to 95 years) were included between February 2006 and October 2010. The patients were classified into two groups as those with and without progression according to the National Institute of Health Stroke Scale (NIHSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, these two studies did not analyze the effect of the craniocervical AS on the occurrence of ND in their study subjects. Several works found that craniocervical atherosclerotic conditions were correlated with the occurrence of ND in patients with ischemic stroke (14,23,24) , thus we further analyzed the relationship of the craniocervical AS with the occurrence of ND in patients with SVO stroke in the present study. We demonstrated that both the presence and the number of craniocervical AS are predictors of ND in patients with SVO stroke.…”
Section: Discussionmentioning
confidence: 96%
“…However, these two studies did not analyze the effect of the craniocervical AS on the occurrence of ND in their study subjects. Several works found that craniocervical atherosclerotic conditions were correlated with the occurrence of ND in patients with ischemic stroke (14,23,24) , thus we further analyzed the relationship of the craniocervical AS with the occurrence of ND in patients with SVO stroke in the present study. We demonstrated that both the presence and the number of craniocervical AS are predictors of ND in patients with SVO stroke.…”
Section: Discussionmentioning
confidence: 96%
“…The impact of pneumonia on the results of treatment, including post-stroke complications, length of stay, status at discharge, and 3-month mRS and BI scores, was also investigated. For stroke complications, progressive stroke was defined as the gradual worsening of neurological function (NIHSS score increase �4) during the 72 hours after stroke onset from an ongoing ischemic process [35][36][37][38][39][40]; brain edema was diagnosed when the patient had a new neurological deficit from brain swelling that was seen in a brain image [41]; and symptomatic intracranial hemorrhage was defined as any intracranial hemorrhage with neurologic deterioration, as indicated by an NIHSS score of �4 points higher than the baseline value [42]. The characteristics of all patients who developed SAP were examined in detail.…”
Section: Methodsmentioning
confidence: 99%
“…With more than 800,000 cases occurring every year, stroke has become the fifth leading cause of death in the United States ( Feigin et al, 2016 ; Jamthikar et al, 2021 ). Among them, ischemic stroke (IS) is the most common type of stroke accounting for 87%, which caused irreversible damage through a variety of cerebral blood supply disorders to the local brain tissue ( Sümer and Özön, 2017 ; Du et al, 2020 ; Qin et al, 2020 ; Tan et al, 2020 ; Salazar-Camelo et al, 2021 ). In clinical practice, conventional treatment measures, such as oxygen inhalation, controlling infection, and lowering intracranial pressure, and specialized treatments, such as early thrombolysis, antiplatelet, anticoagulation, and defibrosis, have certain neurological side effects ( Amr et al, 2016 ; Sarmiento et al, 2019 ; Cheng et al, 2020 ; Herpich and Rincon, 2020 ; Hill, 2020 ).…”
Section: Introductionmentioning
confidence: 99%